(untitled) (Global Journal of Medical Research, 2020)
Acute Appendicitis is a surgical emergency. Patients present with pain in right lower abdomen, with other symptoms like nausea/vomiting, fever, diarrhoea, urinary symptoms. Diagnosis is based on a multimodality approach that includes, clinical, radiological and pathological findings. Alvarado Score helps determine the severity of infection, confirm diagnosis and guide further management. Management is either conservative with antibiotics or surgical depending on severity. However approach to surgical management has changed with the ongoing Covid-19 pandemic. It has necessitated categorisation of surgical procedures into essential and non essential to limit risk to both patient and surgical team and also for prioritization of resources to the rising, continued spread of Covid-19. We present a prospective study of 25 cases of appendicitis presenting during the Covid Pandemic between 15th March and 30th May to our hospital, with an intent to try conservative management for all patients except in the presentations with complications like perforation, abscess or the presence of fecolith or poor response to conservative management. Patients not amenable to conservative management were treated by Open appendicectomy.